GIS implementation in Malaysian statutory development plan system - Abdullah, Muhammad Faris; Abdullah, Alias; Zahari, Rustam Khairi (IGI Global, 2010)
The chapter presents the current state of GIS implementation in Malaysian development plan system. It offers an overview of GIS implementation worldwide, touching briefly on the history of GIS, planners’ early acceptance of the system, factors that promote GIS implementation, level of usage among planners, and factors that impede successful GIS implementation. At the end, the chapter provides a comparison between the state of GIS implementation in Malaysian statutory development plan system with the state of GIS implementation worldwide. The evidence was derived from three main sources: literature, empirical observation of GIS implementation in Malaysia, and a survey conducted in 2008.